Marketing management - Kotler, Philip; Keller, Kevin Lane (Upper Saddle River, NJ : Pearson Prentice Hall, 2006)
This text reflects changes in marketing theory and practice ... It is dedicated to helping companies, groups, and individuals adapt their marketing strategies and management to the marketplace realities of the twenty-first century.
Includes bibliographical references and index.
oif 17/02/15
Loan
Keywords: Marketing